Internet-of-Things based Home Automation System using Smart Phone - Zubair Sharif (Sir Syed University Research Journal of Engineering and Technology)
Smart homes can be of great benefit for both, energy and water management which not only helps to save money but can be highly beneficial for the environment. Such smart automation not only offers optimum consumption of these resources but also leads to higher comfort and conveniences for the users and residents. Recent developments in sensing, networking and communication technologies offering new and advanced forms to link a variety of things around us even with the people. Further, integration of internet of things (IoTs) services by embedding intelligence into these sensors and actuators and connecting them smartly are gaining great popularity to enhance the comfort and quality of life. This paper presents a flexible and low-cost home automation system using various sensors to control the commonly used home appliances and devices where IP connectivity is provided to access and manage them remotely. For this purpose, an Android-based app is developed which can be installed on any smartphone in order to monitor and control the devices from any location. The evaluation of the integrated sensors with the devices and switches shows that the system can offer great automation to achieve the idea of smart homes.